Developing Scalable Series 40 Applications : a Guide for Java Developers - Yuan, Michael; Sharp, Kevin (Addison-Wesley Professional, 2004)
"I have had the good fortune to be involved with mobile Java from the very beginning, and I know what it takes to be successful in this marketplace. This book will help you be successful with mobile Java application design and development. If you take the information inside and sprinkle it with some imaginative application ideas, you will have a winning combination."--Jon Bostrom, Senior Director, CTO Java Technology Platforms, Nokia The First Official End-To-End Solutions Guide for Every Nokia Series 40 Developer Nokia's Series 40 Developer Platform gives Java developers access to the world's highest-volume, fastest-growing, and most exciting mobile markets. Nokia sells close to 100 million units within their Developer Platform families every year, and the Series 40 Developer Platform is the highest-volume platform in the family. Success on this platform is crucial for the commercial success of any mobile application. Knowledge of the Series 40 Developer Platform can be applied to the Java environment on all Nokia Developer Platform devices, including Series 60 devices. Fully reviewed by Nokia's subject matter experts, this book covers the entire development process-from design and coding through testing and deployment. The authors walk you through eleven complete example applications, presenting downloadable client and server source code that you can use to jump-start virtually any project. Along the way, the authors illuminate the technical underpinnings of Series 40, review crucial architectural issues, introduce key mobile design patterns, discuss scalability and device optimization strategies, and offer dozens of best practices and tips-many of which have never before been published. Coverage includes Identifying your best opportunities and killer applications for mobile development Building effective MIDP 2.0 user interfaces for devices built on the Series 40 Developer Platform Building animated mobile games Handling persistent and networking data Proven techniques for scaling and optimizing applications across devices © Copyright Pearson Education. All rights reserved.